2017
DOI: 10.1155/2017/3842659
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Driven Automatic Detection of Lobulation Imaging Signs in Lung CT

Abstract: Computer-aided detection (CAD) of lobulation can help radiologists to diagnose/detect lung diseases easily and accurately. Compared to CAD of nodule and other lung lesions, CAD of lobulation remained an unexplored problem due to very complex and varying nature of lobulation. Thus, many state-of-the-art methods could not detect successfully. Hence, we revisited classical methods with the capability of extracting undulated characteristics and designed a sliding window based framework for lobulation detection in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Traditionally, the evaluation of lobulation signs was made on subjective judgment. But given its important role in identifying the nature of SPNs, quantitative evaluation of lobulations, bending energy, and bigger rectangles overlapping, have been developed in recent years 26 . In this recommendation, the border of nodules was considered for SPN evaluation and we defined a positive border as either a spiculation or a lobulation.…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, the evaluation of lobulation signs was made on subjective judgment. But given its important role in identifying the nature of SPNs, quantitative evaluation of lobulations, bending energy, and bigger rectangles overlapping, have been developed in recent years 26 . In this recommendation, the border of nodules was considered for SPN evaluation and we defined a positive border as either a spiculation or a lobulation.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of lobulation sign might be as follows: First, the differentiation degree and growth rate of each part of the tumour are not same. Secondly, the connective tissue, blood vessels and bronchi in the lungs impede tumour growth [37,38]. We consider that the pull of the surrounding lung tissue on the lobulated lesions and the inflammation caused by the lesion led to the formation of some small air spaces in the surrounding lung tissue.…”
Section: Tablementioning
confidence: 99%
“…Signs are also called “CT features,” “CT manifestation,” “CT patterns,” or sometimes “CT findings” [21]. Lobulation signs [22, 23], spiculation signs [15, 2428], and some texture signs [29, 30] play crucial roles in radiologists' ability to differentiate benign from malignant nodules [31, 32]. Noncentral calcification, such as punctate sign or eccentric sign calcification, usually indicates that a nodule is malignant [3335].…”
Section: Introductionmentioning
confidence: 99%
“…Various works on the CAD based on CT signs have been published. Han G et al [22] designed a sliding-window-based framework to detect lobulation sign. Suzuki K et al [39] developed a computer-aided diagnostic (CAD) scheme to distinguish benign from malignant nodules in LDCT scans using a massive training artificial neural network (MTANN) and concluded that spiculation sign is a highly differentiated feature for distinguishing benign from malignant nodules.…”
Section: Introductionmentioning
confidence: 99%